The Impact of the weather factor on the battle of 1st Infantry Division Tadeusz Kościuszko at Lenino - Anduła, Kamil (Armia kontra natura, 2020)
The Battle of Lenino took place between October 12 and 17, 1943. During the five days of fighting, the Soviet 33rd Army made a series of attempts to break German defence positions at the Miereja River. During the first two days the Polish 1st Infantry Division was involved. In the polish historiography, the issue of the weather conditions during the Lenino battle has not been a subject of scientific analysis. Based on new sources from German and Russian archives, it became possible to reconstruct the weather conditions during the battle. A new data give a picture of the relatively good weather conditions which gave the advantage for the German side. The command of the 33rd Army were not respond flexibly to changing weather. Besides that before the battle, a group of the Polish deserters revealed the date of the attack. As a result, the Germans gathered strong air force. Taking advantage of the cloudless weather, Luftwaffe gave a strong support to ground forces. It was an important reason of German victory at Lenino.